Access points an institutional theory of policy bias and policy complexity - Ehrlich, Sean D. (New York ; Oxford : Oxford University Press, 2011)
'Access Points' develops a theory about how democratic institutions influence policy outcomes. It argues that the more points of access that institutions provide to interest groups the cheaper lobbying will be and, thus, the more lobbying will occur.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pressure groups; Lobbying; Trade regulation; Fiscal policy; Banks and banking -- Government policy; Environmental policy